2021
DOI: 10.3390/land10080795
|View full text |Cite
|
Sign up to set email alerts
|

Tourism, Water Pollution, and Waterway Landscape Changes in a Traditional Village in the Huizhou Region, China

Abstract: Based on archival research, non-participatory observation, and semi-structured interviews, this paper examined waterway landscape changes mainly caused by tourism development in Hongcun, a traditional village in the Huizhou region, China, and how the locals have responded to water pollution in order to achieve landscape sustainability. It is found that the physical structure of the waterways of Hongcun Village has been well preserved, but the water pollution caused by tourism, with a combination of changes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The nature of this type of impact was an interaction between natural tourism resources and landscape that influenced changes. Thus, when natural tourism resources change, the landscape is affected and vice versa (Chen et al, 2021 ; Heslinga et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The nature of this type of impact was an interaction between natural tourism resources and landscape that influenced changes. Thus, when natural tourism resources change, the landscape is affected and vice versa (Chen et al, 2021 ; Heslinga et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative research results surrounding Hypotheses H4 and H5 reveal the rich sense of pride among residents of Hui-style and Min-style architectures. For Hui-style residents, pride arises from economic stability brought by tourism, support from government policies, and the transmission of family honor and traditional arts through generations [74]. These factors together form a sense of pride rooted in economic prosperity and cultural stewardship.…”
Section: Interpretation With the Previous Literaturementioning
confidence: 99%
“…It is noteworthy that architectural culture was identified as a second prominent component of ancient villages' genius loci. This finding suggested that most tourists find cultural resonance in the ancient village tourism experience, in 'the wisdom of traditional human settlement culture' [71,72]. Urban tourists not only visit ancient villages to relieve homesickness, but also to help their children learn about ancient village history and culture [14,15].…”
Section: Theoretical Implicationsmentioning
confidence: 99%